Geographical Indications of Turkish Olive Oils : Evaluation of Quality and Sensory Properties of Thirty EVOOs From 4 Different Regions By Acredited Turkish Sensory Panel And Quality Parameters - B.Özçelik, D. Arucu, S. Ö. Ünsal, E.F. Aydar, Z. Mertdinç (International Journal of Advanced Science and Technology, 2020)
The aims of this study are to characterize the physical, chemical, and sensory properties of Turkish olive oils, to provide characterization according to both variety and the region, and to examine the factors affecting its quality. In this study, the physical, chemical, and sensory properties of 30 different Turkish olive oils including four geographically indicated types (Mut, Nizip, Ayvalık and Edremit olive oils) from five different regions are evaluated statistically and the effects of physical and chemical properties on the sensory characteristics are measured. In this study, free fatty acid, peroxide value, specific UV absorbance, total phenolic content and color measurements have been evaluated in order to determine the physical and chemical properties of oils according to related regulations. Sensory analysis has been performed by total of 8 international tasters accredited by the IOOC. As a result of correlation analysis between these analysis, a strong positive correlation between pungency & bitterness and also total phenol & pungency were found. In another perspective, a strong negative correlation between fruity and rancid property has been resulted.  It is expected that the results obtained in the study will contribute to the creation of databases for the olive oil sector and  geographical indication studies of Turkish EVOOs.